Integration of Innovative Technologies in the Digital Strategy of Platforms based on Systems Thinking - Maslak, Olga; Pochtovyuk, Andrii; Grishko, Natalya; Yakovenko, Yaroslava; Hlazunova, Olha (Integracja innowacyjnych technologii w cyfrowej strategii platform opartej na myśleniu systemowym, 2023)
This paper explores the strategic integration of innovative technologies within platforms grounded in systems thinking principles. Systems thinking provides a holistic approach to understanding complex interactions, while agile methodologies promote adaptability and responsiveness. As prominent technology enterprises continue moulding the digital landscape through cloud gaming, subscription models, and integrated ecosystems, the prominence of systems thinking becomes evident as a guiding principle. By gaining a holistic comprehension of the interlinked dynamics within digital systems, technology companies can deftly maneuver through intricacies, foster innovation efficiently, and furnish users with seamless and enhanced digital encounters. The paper's contributions lie in its comprehensive exploration of the integration of innovative technologies in platforms based on systems thinking and agile methodologies. It provides a valuable framework for practitioners and researchers seeking to enhance their digital strategies and offers valuable insights into the strategic integration of innovative technologies within platforms rooted in systems thinking and agile principles. The study combines theoretical foundations with practical examples, making it a valuable resource for organizations looking to navigate the complexities of the digital era.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 63-73
Keywords: systems thinking; innovation; innovative technologies; agile methodologies; digitalisation; platforms; myślenie systemowe; innowacja; innowacyjne technologie; metodyki zwinne; cyfryzacja; platformy